Identification and Analysis of Technology Emergence Using Patent Classification - Eusebi, Christopher A. (RAND Corporation, 2014)
This report describes a new method for detecting development of commercial interest in technology areas (referred to as technology emergence) by analyzing the network of connections among different technology areas, using the definitions set forth by the U.S. Patent and Trademark Office. Technology emergence is observed through quantitative analysis of the cumulative number of filings in a specific technology area.